Antimicrobial activity of microfungi from maritime Antarctic soil - Abneuf, M.A.; Krishnan, A.; Aravena, M.G.; Pang, K.L.; Convey, P.; Mohamad-Fauzi, N.; Rizman-Idid, M.; Alias, S.A. (EMUNI Press, 2016)
The search for cold-adapted and cold-active fungi in extreme environments provides the potential for discovering new species and novel bioactive compounds. In this study, soil samples were collected from Deception Island, Wilhelmina Bay (north-west Antarctic Peninsula, Graham Land) and Yankee Bay (Greenwich Island), maritime Antarctica, for the isolation of soil fungi and determination of their antimicrobial activity. The soil-plate method, agar block, disc diffusion and broth micro-dilution assays were applied to characterize the thermal classes and antimicrobial activity of the isolated fungi. A total of 27 isolates of fungi were obtained from 14 soil samples, including 13 Ascomycota, 4 Zygomycota and 10 anamorphic fungi. Cold-active (psychrotolerant) fungi predominated over cold-adapted (psychrophilic) fungi. In the antimicrobial assay, 16 isolates showed substantial inhibitory activity against test bacterial pathogens. Ethyl acetate extracts of 10 competent isolates showed significant inhibition of bacterial pathogens. Antifungal activity was observed in the disc diffusion assay, but not in the agar block assay. Minimum inhibitory, bactericidal and fungicidal concentrations were determined using the broth micro-dilution method, with an average in the range of 0.78-25 mg ml-1on the test microorganisms. Isolate WHB-sp. 7 showed the best broad spectrum antimicrobial activity, with the potential for biotechnological studies in antibiotic development.